Relative and absolute reliability of shank and sacral running impact accelerations over a short- and long-term time frame - Burke, A.; Dillon, S.; O'Connor, S.; Whyte, E. F.; Gore, S.; Moran, K. A. (Sports Biomechanics, 2022)
Whilst running is hugely popular, running-related injuries (RRIs) are prevalent. High impact loading has been proposed to contribute to RRIs, with accelerometers becoming increasingly popular in estimating segmental loading for injury detection and biofeedback training. However, there is a lack of research examining the reliability of measures of impact acceleration across short- and long-term time periods, both prior to and following exerted running. The aim of this study was to assess the absolute and relative reliability of shank and sacral impact accelerations over a short- and long-term time period. Peak (Peakaccel) and rate (Rateaccel) of impact acceleration at the shank and sacrum were assessed in 18 recreational runners over short- and long-term time frames, across fixed and self-selected speeds. The relative and absolute reliabilities were investigated for pre- and post-exerted states of running. There was high-to-excellent relative reliability, and predominantly moderate absolute reliability for shank and sacrum Peakaccel and Rateaccel in the short- and long-term time frames between pre- and post-exerted states. High to excellent relative reliability of Peakaccel and Rateaccel at the shank and sacrum are appropriate and acceptable measures across short- and long-term time frames. These findings were consistent with different levels of speed and exertion. The minimal detectable change % was large for both sensors and associated measurements, indicating that their use may be limited to intervention studies that elicit large change (>30%) in these measures.